2014
DOI: 10.1155/2014/131756
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Peer Education in Improving HIV Knowledge, Attitude, and Sexual Behaviours among In-School Adolescents in Osun State, Nigeria

Abstract: Introduction. Young people are at the centre of the global HIV/AIDS epidemic. This study therefore aimed to evaluate the effectiveness of peer education in improving HIV knowledge, attitude, and preventive practices among in-school adolescents in Osun State, Nigeria. Methods. This was an intervention study that was carried out among in-school adolescents attending mixed secondary schools in Osun State, Nigeria. The study was in three stages: before intervention, intervention, and after intervention. The impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 28 publications
4
53
0
Order By: Relevance
“…*The studies that surveyed interventions were carried out without the use of theories and models of health education [11][12][13][14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…*The studies that surveyed interventions were carried out without the use of theories and models of health education [11][12][13][14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…In the third month the barbers 'knowledge was assessed again by using the initial questionnaire. The results of this intervention make us to think and pay attention to media campaigns that can increase the public awareness about blood diseases, and training personnel that may harm people through unsafe operations [16].…”
Section: Studies Conducted Without the Use Of Models And Theories Ofmentioning
confidence: 99%
“…The six studies above showed that sexual and reproductive education programs, in general, have positive impact to change teenagers sexual behavior (Adeleye et al, 2014;de Lijster, Felten, Kok, & Kocken, 2016;Denison et al, 2012;Mahat, Scoloveno, & Scoloveno, 2016;Menna, Ali, & Worku, 2015;Odundo, Anjuri, & Odhiambo) and other studies showed no significance between the health education school with sexual behavior (Jennings, Howard, & Perotte, 2014). However one study that shows two sexual behavior indicates that there is a significant one partner's behavior and sexual intercourse to abstain for a year in post © 2017 The author and GRDS Publishing.…”
Section: The Characteristics Studymentioning
confidence: 99%
“…Other studies using a sample large enough, i.e., more than 400 students, while the study only used a total of 155 students. However, when referring to the length of each intervention studies, studies with sma ll sample amount done in a period of 12 months, whereas other studies with a large number of samples but use a shorter intervention time not necessarily able to demonstrate quite right results (Adeleye et al, 2014;Menna et al, 2015).…”
Section: Strengths and Weaknesses In The Evidence Basedmentioning
confidence: 99%
“…In addition, the proportion of men and women reporting high risk sexual intercourse in the state is very high (19% women & 52% men), while 28% of men were reported to have paid for sex on several occasions in the year prior to the report [11]. A study carried out by [12] identified that peer education is an effective intervention approach among in-school youths. Adeomi et al, [12] stated this because the knowledge of the study group increased as compared to the control group as it regards HIV/AIDS.…”
mentioning
confidence: 99%